2018
DOI: 10.3892/ijmm.2018.3749
|View full text |Cite
|
Sign up to set email alerts
|

AQP4‑knockout alleviates the lipopolysaccharide‑induced inflammatory response in astrocytes via SPHK1/MAPK/AKT signaling

Abstract: To date, aquaporin‑4 (AQP4) has been considered as a critical contributor to neuroinflammation, but little is known about the underlying mechanism. Previous studies have shown that a critical enzyme involved in the sphingomyelin cycle, sphingosine kinase 1 (SPHK1), is implicated in inflammatory processes and contributes to chronic neuroinflammation. The present study investigated the role of AQP4 in proinflammatory cytokine release from astrocytes, with an emphasis on the SPHK1/mitogen‑activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The presence of AQP4 seems to play an acute detrimental role, but at a later phase starting from around seven days post injury and for at least one month. AQP4 may play a beneficial role that seems to be related to the inhibition of microglia and promotion of edema resolution [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of AQP4 seems to play an acute detrimental role, but at a later phase starting from around seven days post injury and for at least one month. AQP4 may play a beneficial role that seems to be related to the inhibition of microglia and promotion of edema resolution [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a postmortem study, patients with depression exhibited lower AQP4 mRNA and protein expression in the brain than healthy control [ 16 , 17 ]. AQP4 knockout also revealed negative effects on neuroprotective markers and behavioral outcomes and was associated with increases in inflammatory markers in animal models of depression [ 18 ], indicating that AQP4 exhibits neuroprotective functions in the CNS and against MDD. MMP-9, a proteolytic enzyme related to synaptic plasticity in the brain activates proinflammatory cytokines in neuroinflammation and is released by T cells during immunoreactions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have verified that SphK1 is implicated in the process of inflammation and causes chronic neuroinflammation ( Melendez, 2008 ; Dai et al, 2018 ). Importantly, a recent study has reported that upregulates the SphK1/S1P receptor signaling pathway may be a key factor of astrocytes mediated chronic inflammation in multiple sclerosis, and BBR ameliorated the severity of MS symptom in mouse model through inducing the increase in SphK1 and S1P.…”
Section: Discussionmentioning
confidence: 98%